Pemberdayaan Ibu Balita dalam Pertolongan Pertama Tersedak di Desa Bangun Rejo, Tanjung Morawa, Deli Serdang, 2025 - Kismiasih Adethia; Lisa Putri Utami; Diah Pitaloka; Tia Erviani (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Choking is a significant cause of morbidity and mortality among children, particularly those aged 3 years or younger. According to the World Health Organization (WHO) in 2011, there were approximately 17,537 reported cases of choking, with the majority of these incidents occurring in children aged between 12 to 36 months. In 2013, about 34 children per day were taken to emergency departments due to choking (Pendigrot et al., 2019). Furthermore, in Indonesia, it was reported that around 10% of the 430 infant deaths were caused by choking during breastfeeding (Suartini & Kusniawati, 2020). Given this, the need for effective first aid knowledge, especially among mothers of young children, becomes imperative. This community service activity aimed to empower 27 mothers with toddlers in the village of Bangun Rejo, Tanjung Morawa, Deli Serdang, North Sumatra, on the essential skills for performing first aid in cases of choking. The program was structured in three phases: preparation, implementation, and evaluation. During the implementation, the participants received theoretical lectures, live demonstrations, and informational leaflets on how to perform first aid for choking. Following the training, an evaluation was conducted to assess the mothers' proficiency in performing the procedure. The results showed a promising outcome, with 19 mothers (70.3%) becoming proficient in first aid for choking, while 8 mothers (29.7%) still lacked the necessary skills despite the training. This outcome highlights the importance of continuous education and practice for parents, especially mothers, to ensure that they can act quickly and effectively in emergency situations. This activity is expected to equip mothers with the skills needed to perform first aid for choking as an immediate response before seeking medical assistance, ultimately helping to reduce the risks associated with choking incidents.